Universuri (diz)armonice la Mihai Eminescu. Viziuni exegetice comparatiste [(Dis)Harmonic Universes in Mihai Eminescu’s Work. Exegetical and Comparative Views] - Silviu Mihăilă (Incursiuni în imaginar)
The present study proposes a comparative analysis, particularly a critique of the critics, applied to Mihai Eminescu’s Romantic universe from the point of view of the hermeneutical category of music. Therefore, our research aims at an exegetical intersection of the critical ideas expressed by Zoe Dumitrescu-Bușulenga (co-author Iosif Sava, Eminescu și muzica, București, Editura Muzicală, 1989) and Ioana Em. Petrescu (Eminescu. Modele cosmologice și viziune poetică, Pitești, Paralela 45, 2005) regarding the phases of Eminescu’s literary work and the transformations/ conversions that each creation phase imposes to his harmonic universe. Nevertheless, we are interested in the evolution of the “sweet music of the spheres” – that governs Eminescu’s first literary productions (the first phase of creation) – towards the last phase (the third one) which sets up – according to both Romanian critics – a tragic universe of disharmonic sonorities.